Freezing methods affect the characteristics of large yellow croaker (Pseudosciaena crocea): use of cryogenic freezing for long-term storage - TRUONGHUYNH,Hoa Thanh (2020)
Abstract Large yellow croaker (Pseudosciaena crocea) is the main coastal economic fish in China. After harvesting, the fish is rarely traded as the fresh product, but usually held in cold storage. Therefore, it is important to understand the quality changes occurring during preservation. In this study, freshly collected fishes were frozen by cryogenic (cabinet liquid nitrogen freezer at -40, -60 and -80 °C) and forced convection (ultra-low temperature freezer at -40 °C) freezing and stored at -18 °C for 6 months. Drip loss, relative moisture loss (RML), water holding capacity (WHC), color and texture of frozen fish were evaluated. The results showed that forced convection freezing had significantly higher drip loss and RML values compared to cryogenic freezing. WHC decreased dramatically irrespective of freezing methods employed. Cryogenic freezing at -60 and -80 °C had the highest yellowness values during storage; but the highest springiness, gumminess and shear force values were obtained only at -60 °C. We conclude that cryogenic freezing at -60 °C is appropriate for long-term storage of large yellow croaker.